Development of a novel approach multiplex late-pcr electrochemical-enzyme based dna sensor for sequence specific detection of vibrio cholerae - Yean, Chan Yean (Pusat Pengajian Kesihatan, 2015)
Phase 1: Development of a Multiplex Linear-After-The-Exponential (LATE)- Polymerase Chain Reaction (PCR) • To design specific primers and optimize a multiplex LATE-PCR which is capable of simultaneously detecting the presence of V. cholerae, as well as cholera toxin and internal control genes. Phase 2: Development of a Mixed Self-Assembled Monolayer (SAM) on Disposable Screen-Printed Gold Electrode (SPGE) • To design thiol-modified capture probe for sequence-specific hybridization with target LATEPCR amplicons. • To optimize the immobilization of capture probe DNAs on gold electrode surface using Self- Assembled Monolayer (SAM) system. Phase 3: Development of a Multiplex Electrochemical-Enzyme based DNA sensor • To optimize the hybridization of labeled LATE-PCR amplicons to the capture probe DNAs. • To optimize the simultaneous detection of multiple redox reactions catalyzed by alkaline phosphatase and horseradish peroxidase by amperometry. Phase 4: Evaluation of the Multiplex Electrochemical-Enzyme based DNA sensor • To perform analytical evaluation of the multiplex electrochemical DNA hybridization genosensor. • To evaluate the performance of the multiplex electrochemical DNA hybridization genosensor using clinical samples. Objective Achieved (Please state the extent to which the project objectives were achieved) Phase 1: Development of a Multiplex Linear-After-The-Exponential (LATE)- Polymerase Chain Reaction (PCR) • To design specific primers and optimize a multiplex LATE-PCR which is capable of simultaneously detecting the presence of V. cholerae, as well as cholera toxin and internal control genes -100% achieved as per planned Phase 2: Development of a Mixed Self-Assembled Monolayer (SAM) on Disposable Screen-Printed Gold Electrode (SPGE) • To design thiol-modified capture probe for sequence-specific hybridization with target LATEPCR amplicons.-100% achieved as per planned • To optimize the immobilization of capture probe DNAs on gold electrode surface using Self- Assembled Monolayer (SAM) system -100% achieved as per planned Phase 3: Development of a Multiplex Electrochemical-Enzyme based DNA sensor • To optimize the hybridization of labeled LATE-PCR amplicons to the capture probe DNAs - 100% achieved as per planned • To optimize the simultaneous detection of multiple redox reactions catalyzed by alkaline phosphatase and horseradish peroxidase by amperometry -100% achieved as per planned Phase 4: Evaluation of the Multiplex Electrochemical-Enzyme based DNA sensor • To perform analytical evaluation of the multiplex electrochemical DNA hybridization genosensor -100% achieved as per planned • To evaluate the performance of the multiplex electrochemical DNA hybridization genosensor using clinical samples -100% achieved as per planned